Obesity and Co-morbid Conditions Are Associated with Specific Neuropsychiatric Symptoms in Mild Cognitive Impairment - Sanderlin, Ashley H.; Todem, David; Bozoki, Andrea C. (Frontiers in Aging Neuroscience, 2017)
Background: Neuropsychiatric symptoms (NPS) in MCI, and midlife obesity increase the likelihood of developing Alzheimer’s disease. It is unknown whether obesity or related health conditions modify the risk of NPS or severity of cognitive impairment in MCI. Methods: One hundred and thirteen subjects with MCI were assessed near the time of MCI diagnosis. The sample was divided by BMI and related disorders, type-2 diabetes (T2D) and obstructive sleep apnea (OSA) to measure the relationship of these groups with NPS and severity of MCI. Neuropsychiatric symptoms scores were evaluated based on the Neuropsychiatric Inventory-Questionnaire (NPI-Q) and Geriatric Depression Scale, along with NPI-Q clusters. MCI-severity was estimated based on a composite z-score of neuropsychological tests. Results: Obese and overweight subjects represented 65% of the sample and were on average 7 years younger than normal weight subjects. The presence of obesity, T2D and OSA status modified the prevalence and severity of specific NPI-Q symptom clusters, specifically affective symptoms were more frequent across groups and severe in OB and T2D. Total NPS scores were higher for subjects with T2D and OSA although MCI-severity did not differ across groups. Conclusions: MCI subjects with obesity, T2D and OSA demonstrated a higher susceptibility to psychopathologic changes.